2017
DOI: 10.1371/journal.pone.0189750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the EGFR polymorphism R497K in two cohorts of neoadjuvantly treated breast cancer patients

Abstract: Pathological response of breast cancer to neoadjuvant chemotherapy (NAC) presents great variability, and new prognostic biomarkers are needed. Our aim was to evaluate the association of the epidermal growth factor receptor gene (EGFR) polymorphism R497K (rs2227983) with prognostic features and clinical outcomes of breast cancer, including the pathological response to NAC and the recurrence-free survival (RFS). Tumoral complete response (tCR) was defined by no remaining invasive cancer in the excised breast, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(49 reference statements)
0
3
2
Order By: Relevance
“…In the present study, we did not find significant associations between EGFR rs2227983 and clinicopathological features. In contrast, some studies showed that rs2227983 was statistically associated with differentiation degree (tumour grade) and lymph node involvement, which was not found in our study [19,34,35]. Interestingly, Sobral-Leite et al [34] reported that a poorly differentiated tumor was more common in patients with GA and AA genotypes.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the present study, we did not find significant associations between EGFR rs2227983 and clinicopathological features. In contrast, some studies showed that rs2227983 was statistically associated with differentiation degree (tumour grade) and lymph node involvement, which was not found in our study [19,34,35]. Interestingly, Sobral-Leite et al [34] reported that a poorly differentiated tumor was more common in patients with GA and AA genotypes.…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast, some studies showed that rs2227983 was statistically associated with differentiation degree (tumour grade) and lymph node involvement, which was not found in our study [19,34,35]. Interestingly, Sobral-Leite et al [34] reported that a poorly differentiated tumor was more common in patients with GA and AA genotypes. While, in the study by Kallel et al [19], a poorly differentiated tumor was more frequently diagnosed in patients who had GG genotype.…”
Section: Discussioncontrasting
confidence: 98%
“…In many independent studies using samples representing different malignancies such as lung, breast, renal, and prostate, the role of excessive EGF and EGFR activities in the carcinogenesis mechanism has been demonstrated. (Fujiwara, Eguchi, Sogawa, Ono, Murakami, Ibaragi, Asaumi, Calderwood, et al, 2018; Liu et al, 2015; Sobral‐Leite et al, 2017; Teixeira et al, 2014). In addition, increased signaling from EGF and EGFR has been shown in OSCC (Fujiwara, Eguchi, Sogawa, Ono, Murakami, Ibaragi, Asaumi, Okamoto, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular markers have been identified to predict responses to NAC, including p53 ( 12 ), cytokeratin ck5/6 ( 13 ), epidermal growth factor receptor ( 14 ), Ki67 ( 15 ), and methylation of Ras association domain family 1 isoform A ( RASSF1A ) and WNT inhibitory factor-1 ( WIF-1 ) ( 16 ) in serum. However, biomarkers that can accurately predict the response to NAC in clinical settings remain limited.…”
Section: Introductionmentioning
confidence: 99%